Proficiência motora de escolares do PIBID em turmas de anos iniciais - Santos, Eurico Barcelos dos (2016)
INTRODUCTION: The Motor Development (MD) is a sequential and dynamic process, subordinate on the interaction between biology, environment and task. The interaction between biological and environmental constraints is what determines the MD. The school environment is an important social environment, which can and should contribute to MD. This way, the teaching work needs to be subsidized by theorical support and provide reliable data about the purpose for motor aspects to justify the inclusion of this curricular component in the early years. OBJECTIVE: Analyze the efficiency of a program based on a Guided Play in physical education classes for PIBID’s students between six and eight years old through the assessment of motor proficiency, before and after a intervention. METHODS: 155 students between six and eight years-old participated in this research project, who attends four public schools in Santa Maria – RS. These schools are participating in the Programa Institucional de Bolsas de Iniciação à Docência (PIBID). This study had a Pre-experimental delineation. To obtain the data relating to aspects of Motor Proficiency were used the protocol Bruininks-Oseretsky Test of Motor Proficiency (1978). The interventional period has apllied a program based on Games inside and outside the school (VENÂNCIO e FREIRE, 2005) with a duration of four months, frequency of one lesson a week, totaling 16 lessons. For statistics analysis was used SPSS for Windows 20.0 a descriptive way (average and standard deviation). For detecting differences in pre- and post-tests were applied Anova Two Way for repeated measures, applying Test t pareado where significances were identified. Confidence interval was adopted in 95% and lower levels of significance 5% were considered statistically significant. RESULTS: Results show that a program based on Guided Play can cause significant differences in abilities Agility (≤0,001), Lower Limb Strength (≤0,001), Response Speed (≤0,001), Viso-Motor Coordination (≤0,001), Motor Fine (≤0,028), Manual Dexterity (≤0,001) and Motor Proficiency (≤0,001). CONCLUSION: When analysing the results it can be inferred that a program of Guided Play is capable producing significant responses in motor aspects and specially in Motor Proficiency, thus indicating an importance of using qualified methods and mainly provide children/students the opportunity to interact and promote MD satisfactorily.